ANALISIS PENGELOLAAN PERMINTAAN DAN KAPASITAS PRODUKSI PADA USAHA TYFLORIST.ID DI KOTA BATAM - Febby Huang; Jenny Lim; Thomas Eddison; Winson Tan; Kevin Salim (Bajang Institute, 2022)
Tyflorist.id is one of the MSME in the service sector in batam that moves online, Tyflorist.id has a product in the form of a bouquet. MSME Tyflorist.id has failed several times to meet customer demands. This problem requires the right solution to minimize expenses. This research was conducted by analysing the workings of MSME to find the right solution. The results of this study indicate that Tyflorist.id has failed to meet customer demands due to sudden changes in desires, to anticipate this, Tyflorist.id provides one time revisions in a product.